Succinate dehydrogenase deficiency in a chromaffin cell model retains metabolic fitness through the maintenance of mitochondrial NADH oxidoreductase function. Issue 1 (22nd November 2019) - Kľučková, Katarína; Thakker, Alpesh; Vettore, Lisa; Escribano-Gonzalez, Cristina; Hindshaw, Rebecca L.; Tearle, Jacqueline L. E.; Goncalves, Judith; Kaul, Baksho; Lavery, Gareth G.; Favier, Judith; Tennant, Daniel A.
Abstract: Mutations in succinate dehydrogenase (SDH) lead to the development of tumors in a restricted subset of cell types, including chromaffin cells and paraganglia. The molecular basis for this specificity is currently unknown. We show that loss of SDH activity in a chromaffin cell model does not perturb complex I function, retaining the ability to oxidize NADH within the electron transport chain. This activity supports continued oxidation of substrates within the tricarboxylic acid (TCA) cycle. However, due to the block in the TCA cycle at SDH, the high glutamine oxidation activity is only maintained through an efflux of succinate. We also show that although the mitochondria of SDH‐deficient cells are less active per se, their higher mass per cell results in an overall respiratory rate that is comparable with wild‐type cells. Finally, we observed that when their mitochondria are uncoupled, SDH‐deficient cells are unable to preserve their viability, suggesting that the mitochondrial metabolic network is unable to compensate when exposed to additional stress. We therefore show that in contrast to models of SDH deficiency based on epithelial cells, a chromaffin cell model retains aspects of metabolic "health, " which could form the basis of cell specificity of this rare tumor type.